Coenzyme Q10 and embryonic development: a potential role in reproductive medicine - A. U. Khamadyanova; R. M. Mannanov; D. M. Smakova; F. I. Musaeva; D. G. Bedelov; A. E. Ibragimov; A. A. Rusinova; M. M. Salikhova; S. V. Shtukaturova; T. V. Doroshenko; M. V. Fattakhova; M. K. Rakhimova; et al. (Акушерство, гинекология и репродукция)
Maternal mitochondria provide energy to the embryo through oxidative phosphorylation before blastocyst implantation, where intracellular energy is mainly supplied by glycolysis. Thus, it is obvious that mitochondria play a crucial role in providing energy for embryogenesis. Coenzyme Q10 (CoQ10) is a powerful endogenous membrane-localized antioxidant that protects circulating lipoproteins from lipid peroxidation. The results of several recent clinical studies have shown that exogenous CoQ10 supplements exert antioxidant effects and may be a potential therapy to reduce oxidative stress. CoQ10 deficiency increases the risk of impaired embryonic development; however, this relationship remains unclear. Given that CoQ10 level is influenced by enzymes involved in its synthesis, it is difficult to say whether the disorders are caused by CoQ10 deficiency or directly result from defects in the target gene. It has been shown that in the absence of CoQ10, ATP synthesis decreases in parallel with increased oxidative stress in mitochondria, two biological events which affect embryonic development. The review highlights the importance of CoQ10 as an antioxidant for improving egg quality, and also emphasizes its key role in embryonic development. It is necessary to conduct further studies aimed at studying metabolic changes during embryogenesis, as well as the mechanism of CoQ10 effects.